Determinants of online reservation acceptance: an empirical study - Ab. Aziz, Noor Hidayah; Mohamed, Intan Salwani; Omar, Normah (Penyelidikan & Jaringan Industri, 2012)
The evolution of E-commerce has created a competitive environment that changed the way of doing business. Travel-related industries such as hoteliers, airlines, and travel agencies compete effectively in the current business environment by adopting online reservation systems. Despite millions of dollars spent on web-technology investment, there are customers who prefer to continue using the traditional method of business transactions. This highlights the need to study the determinants of user acceptance of online reservations. Grounded in the extended Technology Acceptance Model (TAM), the current study attempts to investigate the causal link between individual differences in computer self-efficacy (CSE), perceived ease of use (PEOU), perceived usefulness (PU), perceived credibility (PC), and behavioral intention (BI) in the Malaysian environment. Results of Structural Equation Modeling (SEM) demonstrate that CSE has a significant relationship with PU, PU and PC have a significant influence on BI, PEOU has no significant influence on BI, and CSE does not predict PC and PEOU.